(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Тhis paper presents a conceptual analysis of the notion of tolerance in the context of dialogue EastWest, and explains the need for disclosure of the meaning and significance of concepts. The author examines the mutual influence and the development of culture, civilization, ethnic group, nation, identity in the process of finding the truth in the context of the dialogue of civilizations between East and West. Key words: values, East-West, tradition, identity, culture and civilization.